A remarkable toughening high-entropy-alloy wire with a bionic bamboo fiber heterogeneous structure. (15th March 2023) - Zhou, Shichao; Dai, Chunduo; Hou, Huaxing; Lu, Yiping; Liaw, Peter K.; Zhang, Yong
Abstract : The bionics structure inspires a new design approach for the strength-toughness trade-off of metallic materials. In this study, a bionic bamboo fiber heterogeneous microstructure was successfully constructed in an ultrafine-grained eutectic high-entropy alloy, AlCoCrFeNi2.1, by multi-pass cold-drawing and subsequent annealing. Such a bionic microstructure possesses a hard-B2 fiber along the axial direction embedded in the soft-face-centered-cubic (FCC)-matrix, achieving an excellent synergy of strength and ductility. Originating from this structural heterogeneity, deformation incompatibility and strain gradient generated between the B2 fiber and FCC matrix phases, causing the formation of the significant hetero-deformation-induced hardening. This hardening effect not just reinforced the FCC matrix and contributed to the excellent yield strength, also enhanced high strain-hardening and postponed the strain-localization of the brittle-B2 fiber, and furthermore increased the tensile ductility. Graphical abstract: Image, graphical abstract